Results from the translation and adaptation of the Iranian Short-Form McGill Pain Questionnaire (I-SF-MPQ): preliminary evidence of its reliability, construct validity and sensitivity in an Iranian pain population - Adelmanesh Farhad; Arvantaj Ali; Rashki Hassan; Ketabchi Seyedmehdi; Montazeri Ali; Raissi Gholamreza (BMC, 2011)
Abstract Background The Short Form McGill Pain Questionnaire (SF-MPQ) is one of the most widely used instruments to assess pain. The aim of this study was to translate and culturally adapt the questionnaire for Farsi (the official language of Iran) speakers in order to test its reliability and sensitivity. Methods We followed Guillemin's guidelines for cross-cultural adaption of health-related measures, which include forward-backward translations, expert committee meetings, and face validity testing in a pilot group. Subsequently, the questionnaire was administered to a sample of 100 diverse chronic pain patients attending a tertiary pain and rehabilitation clinic. In order to evaluate test-retest reliability, patients completed the questionnaire in the morning and early evening of their first visit. Finally, patients were asked to complete the questionnaire for the third time after completing a standardized treatment protocol three weeks later. Intraclass correlation coefficient (ICC) was used to evaluate reliability. We used principle component analysis to assess construct validity. Results Ninety-two subjects completed the questionnaire both in the morning and in the evening of the first visit (test-retest reliability), and after three weeks (sensitivity to change). Eight patients who did not finish treatment protocol were excluded from the study. Internal consistency was found by Cronbach's alpha to be 0.951, 0.832 and 0.840 for sensory, affective and total scores respectively. ICC resulted in 0.906 for sensory, 0.712 for affective and 0.912 for total pain score. Item to subscale score correlations supported the convergent validity of each item to its hypothesized subscale. Correlations were observed to range from r2 = 0.202 to r2 = 0.739. Sensitivity or responsiveness was evaluated by pair t-test, which exhibited a significant difference between pre- and post-treatment scores (p < 0.001). Conclusion The results of this study indicate that the Iranian version of the SF-MPQ is a reliable questionnaire and responsive to changes in the subscale and total pain scores in Persian chronic pain patients over time.